Strengthening the Financial Performance of MSMEs in Lamongan: Exploring the Relationship Between Digitalization, Financial Literacy, Product Development, Branding Capability and HR Quality with Sales Turnover as a Mediator - Muhtarom, Abid (Universitas Dharma Wacana, 2025)
This research emphasizes the importance of internal factors in strengthening the financial performance of MSMEs and exploring potential mediation mechanisms through sales turnover.With a better understanding of this relationship, MSMEs in Lamongan Regency are expected to optimize their potential and adapt to the demands of the digital era.PLS SEM methodology.This research shows that factors such as digitalization, financial literacy, branding, and the quality of human resources have a significant impact on the financial performance and sales turnover of SMEs in Lamongan.However, some factors such as product development need more attention to improve their effectiveness.Sales turnover has also proven to be a significant mediator in the relationship between these factors and the financial performance of SMEs.The results of this study are expected to provide insights and practical recommendations for SMEs and other stakeholders to improve the financial performance of SMEs in Lamongan.